2017
DOI: 10.1071/an16166
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and lamb losses from pregnancy scanning to lamb marking in commercial sheep flocks in southern New South Wales

Abstract: Perinatal lamb mortality is a major challenge for sheep producers worldwide. Lamb losses from ultrasound pregnancy scanning to lamb marking were assessed in 125 mobs of ewes sourced predominantly from sheep flocks in southern New South Wales. In total, 103 086 lambs were marked from100 165 ewes present at joining. Despite the majority of producers undertaking best-practice ewe management, including ultrasound scanning for pregnancy and preferential feeding of multiple bearing ewes, losses were similar to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
4
15
1
Order By: Relevance
“…The mob size per pen or paddock reported in this study is within the range reported for earlier surveys of commercial flocks at joining or lambing in South Australia, New South Wales or Victoria, Australia, 3,9,10 and New Zealand, 10 indicating that the respondents represent a mix of commercial-scale Australian breeding flocks. The lower than targeted number of responses prevented analysis for any association between husbandry practices and reproductive performance, and also means that the results may not represent the practices of Australian sheep breeders in general.…”
Section: Discussionsupporting
confidence: 77%
“…The mob size per pen or paddock reported in this study is within the range reported for earlier surveys of commercial flocks at joining or lambing in South Australia, New South Wales or Victoria, Australia, 3,9,10 and New Zealand, 10 indicating that the respondents represent a mix of commercial-scale Australian breeding flocks. The lower than targeted number of responses prevented analysis for any association between husbandry practices and reproductive performance, and also means that the results may not represent the practices of Australian sheep breeders in general.…”
Section: Discussionsupporting
confidence: 77%
“…Kleemann et al (2006) suggested that the survival of single and twin lambs born to adult ewes was optimised at mob sizes of approximately 400 ewes. In contrast, Allworth et al (2017) reported that the survival of twin lambs born on commercial farms tended to be lower at mob sizes greater than 200 ewes compared to less than 200 ewes. Higher mob sizes at lambing could therefore decrease lamb survival.…”
Section: Introductionmentioning
confidence: 91%
“…Lambs are solely dependent on their dams for milk for survival in early life, with milk remaining an important source of digestible energy and protein to weaning late in lactation (Hayman et al 1955;Clark 1980). It is well established that perinatal and neonatal lamb loss is a significant issue for sheep farmers (Stafford 2013;Dwyer et al 2016;Allworth et al 2017), and that ewes with defective udders contribute to this loss (Hayman et al 1955;Watson and Buswell 1984). However, there appears to have been little recent scientific investigation of udder morphology in New Zealand.…”
Section: Introductionmentioning
confidence: 99%